RESPECT OF THE ARTICLE 8 OF THE EUROPEAN CONVENTION FOR THE PROTECTION OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS IN THE RECENT CASE LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS - Vojvodic, Jovana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Private and family life represent one of the most intimate and significant aspects of human life. The focus of this paper is the analysis of the right to respect for private and family life, as the element of the protection of Article 8 of the European Convention for the Protection of Human Rights and Fundamental Freedoms. This analysis is primarily conducted through research and interpretation of the European Court of Human Rights case law. The right to private and family life is not an absolute right. On the contrary, states are given the opportunity to restrict its protection, if the conditions explicitly provided by the European Convention for the Protection of Human Rights and Fundamental Freedoms are met. When the applicants consider that the specific state restriction has violated their right to respect for private and family life, it is upon the European Court of Human Rights to decide whether the restriction has been justified, taking into account the facts of the each individual case and the standards set out in its previous case law.
Keywords: European Convention for the Protection of Human Rights and Fundamental Freedoms, European Court of Human Rights, Article 8, private life, family life